Propensity-score-adjusted comparison of Evolut vs. Portico devices for transcatheter aortic valve implantation. Issue 5 (May 2019) - Giordano, Arturo; Corcione, Nicola; Ferraro, Paolo; Pieri, Pietro; Avellino, Raffaella; Frati, Giacomo; De Persio, Giovanni; Altamura, Luca; Tomai, Fabrizio; Biondi-Zoccai, Giuseppe
Abstract : Aims: Transcatheter aortic valve implantation has become an established treatment for severe aortic stenosis, thanks to key improvements achieved by new-generation devices. Their comparative effectiveness and safety are, however, still uncertain. Methods: We queried a prospective registry on transcatheter aortic valve implantation to compare Evolut and Portico devices, focusing on procedural, in-hospital, and mid-term outcomes. Unadjusted and propensity-adjusted analyses were carried out. Results: In all, 233 patients were included, 119 (51.1%) receiving Evolut and 114 (48.9%) Portico. Several differences in baseline and procedural features were evident, including comorbidities, device size, and postdilation (all P  < 0.05). Unadjusted analysis for procedural results showed significant differences in fluoroscopy time, left ventricular ejection fraction, and aortic regurgitation (all P  < 0.05), whereas device and procedural success rates were not significantly different (both P  > 0.05). In-hospital outcomes were not significantly different (all P  > 0.05). Survival analysis for mid-term follow-up (6 ± 7 months) outcomes showed no significant differences in death, stroke, myocardial infarction, major vascular complication, or major bleeding (all P  > 0.05). Conversely, Evolut appeared associated with lower peak and mean aortic gradients (both P  < 0.05), but higher rate of permanent pacemaker implantation ( P  = 0.043). Propensity-score-adjusted analysis largely confirmed the similar performance of the two devices, including peak and mean aortic gradients (both P  > 0.05). However, Evolut continued to be associated even at adjusted analysis with an increased risk of pacemaker implantation ( P  = 0.018). Conclusion: The acute and mid-term comparative safety and effectiveness of Evolut and Portico in experienced hands are similar, with the notable exception of a lower risk of permanent pacemaker implantation with Portico. Abstract : Supplemental Digital Content is available in the text